2019
DOI: 10.3126/bjhs.v4i2.25438
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Instrumental Vaginal Delivery in BP Koirala Institute of Health Sciences

Abstract: Introduc onDelivery which is conducted with the help of instruments either vacuum or Forceps is known as instrumental vaginal delivery (IVD). It is done to prevent the pa ent from impending cesarean sec on and uterine scar which has its implica on in the future pregnancy along with maternal and fetal morbidi es as well. Objec veThis study assessed the risk factors and feto-maternal outcome of instrumental vaginal delivery Methodology ORA 116

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…8 It is also consistent with the frequencies observed in tertiary care hospitals in Kathmandu and Eastern Nepal. 9,10 Our finding is also comparable to that from the United States Birth Registry of 2017 showing rates of 3.1% among 3.86 million. 11 A recent retrospective population-based cohort study of the US birth records showed that forceps and vacuum delivery decreased significantly in the USA from 2005 to 2013 with rates decreasing to as low as 3.1% in recent times.…”
Section: Discussionsupporting
confidence: 86%
“…8 It is also consistent with the frequencies observed in tertiary care hospitals in Kathmandu and Eastern Nepal. 9,10 Our finding is also comparable to that from the United States Birth Registry of 2017 showing rates of 3.1% among 3.86 million. 11 A recent retrospective population-based cohort study of the US birth records showed that forceps and vacuum delivery decreased significantly in the USA from 2005 to 2013 with rates decreasing to as low as 3.1% in recent times.…”
Section: Discussionsupporting
confidence: 86%
“…However, this report is higher than the studies done in India ( 18 ), Nepal ( 31 ), and Nigeria ( 32 – 34 ). In addition, the finding from this review was high compared to a survey conducted by WHO in nine Asian countries which found a prevalence of 3.2% ( 35 ).…”
Section: Discussioncontrasting
confidence: 79%